2002
DOI: 10.1177/009127002401102821
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Comparative Study of Ibuprofen Arginate versus Conventional Ibuprofen in the Treatment of Postoperative Dental Pain

Abstract: The analgesic efficacy of an arginine salt of ibuprofen was compared to one of the commercially available forms of conventional ibuprofen in a 500-patient clinical trial in postoperative dental pain. Patients were administered a single dose of ibuprofen arginate (200 mg or 400 mg), conventional ibuprofen (200 mg or 400 mg), orplacebo in this double-blind, randomized, parallel-group trial. Results demonstrated that ibuprofen arginate was a safe and effective analgesia that was superior to conventional ibuprofen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…[15][16][17] This clinical trial supports the hypothesis that ibuprofen arginate is as efficacious as conventional ibuprofen, but with a faster onset of action. In this study, ibuprofen arginate was shown to have significantly faster pain relief than conventional ibuprofen.…”
Section: Discussionsupporting
confidence: 70%
“…[15][16][17] This clinical trial supports the hypothesis that ibuprofen arginate is as efficacious as conventional ibuprofen, but with a faster onset of action. In this study, ibuprofen arginate was shown to have significantly faster pain relief than conventional ibuprofen.…”
Section: Discussionsupporting
confidence: 70%
“…In terms of SPRID over 6 h, both ibuprofen test formulations were significantly more efficacious than acetaminophen. Previous studies using the post-operative dental pain model have demonstrated that treatment with a different ibuprofen salt formulation, ibuprofen arginate (l-arginine salt of ibuprofen), resulted in faster onset times to analgesia and greater overall efficacy than treatment with conventional (standard) ibuprofen [11,12,19]. The pharmacokinetic profile of the ibuprofen sodium formulation used in this study has been shown to be similar to that of ibuprofen arginate with peak plasma concentrations achieved at approximately 30-40 min, compared with 1-2 h for standard ibuprofen [8,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…For the primary endpoint, data were available for the time to perceptible relief from three studies using ibuprofen arginate [11,12,19]. These data suggested that the time to perceptible relief would be 9 to 14 min for the two test formulations, assuming a similar onset of action to that of ibuprofen arginate.…”
Section: Sample Size Determinationmentioning
confidence: 99%
See 2 more Smart Citations